Chemical characterization and source identification of particulate matter at Ballari (15.15°N, 76.93°E), Karnataka over Southern Indian region. (April 2020) - Shalini, V.; Narasimhulu, K.; Raja Obul Reddy, K.; Balakrishnaiah, G.; Rama Gopal, K.; Lokeswara Reddy, T.; Chakradhar Rao, T.; Elijabetthamma, B.; Manjunatha, C.; Ramakrishna Reddy, R.
Abstract: The present study reports the chemical composition and source identification of the total suspended particulate matter in the sub-urban environment, Ballari. There were 28 particulate matter aerosol sampled between February 2017–July 2018. The surface mass concentration ranged from 103 μg m −3 to 367 μg m −3 with an average value of ~225 ± 65 μg m −3 during the study period. The morphology and elemental composition of aerosol particles were analyzed by using a scanning electron microscope (SEM) coupled with an energy dispersive X-ray system (EDX). From the EDX results aluminosilicate group (Al, Si, K, Fe, Na, Mg, Ti and Ca) contains about ~31% of the total particles, which mainly due to mineral particulate aerosol originate from crustal origin through windblown dust. Further, we also investigated the morphology and chemical composition of total mass concentration during haze (27-03-2018) and clear days (23-02-2018). The SEM pictures show the most notable deposition of spherical particles with smooth surfaces on a hazy day suggesting that the carbon aerosols on haze day were favourable to coagulation of Aitken mode particles, which is consistent with their respective aerosol subtypes captured from Cloud-Aerosol Lidar with Orthogonal Polarization (CALIPSO) satellite over the study region. Inductively coupled plasma optical emission spectrometer (ICP-OES) analysis showed the relative contribution of inorganic ions ( SO 4 2 −, NO 3 −, Na +, Ca 2+, Cl −, NH 4 +, K + ) is higher than others on 1-05-2017 and 01-01-2018 days over the observational site. The relative contribution of non-sea salt SO 4 2 − was abundance (~35%) on both days, indicating the significant anthropogenic influence at this location. The concentration weighted trajectory (CWTs) analysis showed the major sources of particulate matter were soil particles, vehicular emissions, and mining activities surroundings the vicinity of the sampling site. Highlights: The total mass concentration varied from 103 μg m −3 to 367 μg m −3 over Bellary. EDX results showed aluminosilicate group contains about ~31% during study period. ICP-OES analysis confirmed the inorganic ions dominant over study region. CWT results showed the major sources were mining and anthropogenic sources over location.